Familial transmission of human T-cell lymphotrophic virus: silent dissemination of an emerging but neglected infection. - Carlos Araujo da Costa; Karen Cristini Yumi Ogawa Furtado; Louise de Souza Canto Ferreira; Danilo de Souza Almeida; Alexandre da Costa Linhares; Ricardo Ishak; Antonio Carlos Rosário Vallinoto; José Alexandre Rodrigues de Lemos; Luisa Caricio Martins; Edna Aoba Yassui Ishikawa; Rita Catarina Medeiros de Sousa; Maísa Silva de Sousa (Public Library of Science (PLoS), 2013)
BACKGROUND: HTLV-1 is a retrovirus that causes lymphoproliferative disorders and inflammatory and degenerative diseases of the central nervous system in humans. The prevalence of this infection is high in parts of Brazil and there is a general lack of public health care programs. As a consequence, official data on the transmission routes of this virus are scarce. OBJECTIVE: To demonstrate familial aggregation of HTLV infections in the metropolitan region of Belém, Pará, Brazil. METHOD: A cross-sectional study involving 85 HTLV carriers treated at an outpatient clinic and other family members. The subjects were tested by ELISA and molecular methods between February 2007 and December 2010. RESULTS: The prevalence of HTLV was 43.5% (37/85) for families and 25.6% (58/227) for the family members tested (95% CI: 1.33 to 3.79, P = 0.0033). Sexual and vertical transmission was likely in 38.3% (23/60) and 20.4% (29/142) of pairs, respectively (95% CI: 1.25 to 4.69, P = 0.0130). Positivity was 51.3% (20/39) and 14.3% (3/21) in wives and husbands, respectively (95% CI: 0.04 to 0.63, P = 0.0057). By age group, seropositivity was 8.0% (7/88) in subjects <30 years of age and 36.7% (51/139) in those of over 30 years (95% CI: 0.06 to 0.34, P<0.0001). Positivity was 24.1% (7/29) in the children of patients infected with HTLV-2, as against only 5.8% (4/69) of those infected with HTLV-1 (95% CI: 0.05 to 0.72, P = 0.0143). CONCLUSION: The results of this study indicate the existence of familial aggregations of HTLV characterized by a higher prevalence of infection among wives and subjects older than 30 years. Horizontal transmission between spouses was more frequent than vertical transmission. The higher rate of infection in children of HTLV-2 carriers suggests an increase in the prevalence of this virus type in the metropolitan region of Belém.